2017
DOI: 10.1186/s12876-017-0673-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging analysis of brain function in patients with irritable bowel syndrome

Abstract: BackgroundIrritable bowel syndrome (IBS) is a common functional disease of the gastrointestinal tract. The current study aimed to examine the association between visceral hypersensitivity in IBS and cortical activation using functional magnetic resonance imaging (fMRI), and to elucidate the role of psychological factors in the pathogenesis of IBS.MethodsThe present study included 31 patients with IBS and 20 healthy controls. Cerebral function was assessed using fMRI. During imaging, a Sengstaken-Blakemore tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…e MT is an important relay station that receives visceral pain information from the spinal cord and then transmits this information to the cortex through the myelothalamic tract for integration and regulation. Clinical studies have found that activation of the thalamus is increased in patients with IBS depending on the level of rectal expansion, and electroacupuncture was shown to regulate MT activation and participate in the ascending pain transmission pathway of IBS through fMRI technology [6,28,29]. Astrocytes are widely distributed in brain regions, communicating with neurons and participating in the transmission of synaptic signals.…”
Section: Discussionmentioning
confidence: 99%
“…e MT is an important relay station that receives visceral pain information from the spinal cord and then transmits this information to the cortex through the myelothalamic tract for integration and regulation. Clinical studies have found that activation of the thalamus is increased in patients with IBS depending on the level of rectal expansion, and electroacupuncture was shown to regulate MT activation and participate in the ascending pain transmission pathway of IBS through fMRI technology [6,28,29]. Astrocytes are widely distributed in brain regions, communicating with neurons and participating in the transmission of synaptic signals.…”
Section: Discussionmentioning
confidence: 99%
“…In existing studies, various functional mechanisms and biopsychosocial models (Tanaka et al, 2011) related to clinical types have been put forward to detect the pathogenesis of IBS. Recent studies have shown that gastrointestinal dysfunction caused by IBS is associated with the dysregulation of the brain's central and peripheral nervous system (Omalley, 2016;Wang et al, 2017) and may be altered by psychological factors such as stress, anxiety, and depression (Ke et al, 2015). Few of these studies make the effort to utilize functional interaction and segregation to investigate the brain dysfunction mechanism of IBS and those modulated by related treatments such as acupuncture stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Extraintestinal symptoms in the brain, such as cerebral thrombosis and multiple sclerosis in white matter, have been detected (Benjilali et al., 2011; Stovicek et al., 2014), suggesting that the GI tract might have peculiar effects on the brain, despite the remote distance. Furthermore, ulcerative colitis (a subtype of inflammatory bowel disease) (Fan et al., 2019) and other brain–gut axis‐related diseases, such as irritable bowel disease (Wang et al., 2017) and functional constipation (Liu et al., 2020), show anomalies in the ACC. Thus, we hypothesize that the ACC plays an important role in the pathophysiology of CD.…”
Section: Introductionmentioning
confidence: 99%